Digital Business Strategies to Navigate Technological Disruption in 2026 - Gregorius Paulus Tahu; Septimus Adrianus Mali; Narwanto Nurcahyo (Jurnal Ragam Pengabdian, 2026)
This study explores the role of digital business strategies in navigating technological disruption by 2026. The rapid advancement of technologies such as AI, blockchain, and IoT presents both challenges and opportunities for businesses to adapt. The objective is to analyze how companies can implement effective digital strategies to stay competitive in an evolving digital landscape. Utilizing a library research methodology, the study collects data from books, journals, and case studies on digital transformation, disruption, and strategic adaptation. Findings reveal that businesses embracing digital transformation and fostering organizational agility are more successful in leveraging emerging technologies. However, companies face significant barriers such as financial constraints, skills gaps, and resistance to change. The study concludes that adopting a holistic approach to digital strategies, aligning technology with business goals, and investing in continuous innovation are key to overcoming disruption and achieving long-term success.